Radiation dose associated with cerebral CT angiography and CT perfusion: an experimental phantom study - Sabarudin, Akmal; Yusof, M.; Mohamad, M.; Sun, Zhonghua (Oxford University Press, 2014)
A study on the radiation dose associated with cerebral CT angiography (CTA) and CT perfusion (CTP) was conducted on an anthropomorphic phantom with the aim of estimating the effective dose (E) and entrance skin dose (ESD) in the eyes and thyroid gland during different CTA and CTP protocols. The E was calculated to be 0.61 and 0.28 mSv in CTA with 100 and 80 kVp, respectively. In contrast, CTP resulted in an estimated E of 2.74 and 2.07 mSv corresponding to 40 and 30 s protocols, respectively. The eyes received a higher ESD than the thyroid gland in all of these protocols. The results of this study indicate that combining both CTA and CTP procedures are not recommended in the stroke evaluation due to high radiation dose. Application of modified techniques in CTA (80 kVp) and CTP (30 s) is highly recommended in clinical practice for further radiation dose reduction.